Presenting in English : how to give successful presentations / Mark Powell - Powell, Mark (English teacher)
Presenting in English teaches students how to become successful presenters at conferences or meetings. The course is designed for all students who need to use their English in front of audiences of any size. The author, himself a very effective presenter, has organised all the skills, language, and techniques needed to present in public with confidence. The course includes extensive practice activities and is accompanied by two audio CDs. This course has an Answer Key and is designed to be used by students alone or in class. Presenting in English has several unique features which make it exceptionally practical